Biotoxicity study of bone cement based on a functionalised multi-walled carbon nanotube-reinforced PMMA/HAp nanocomposite. (10th August 2009) - Singh, Manoj K.; Marques, Paula A.A.P.; Sousa, Antonio C.M.; Gracio, Jose; Silva, Virgilia; Goncalves, Paula; Ferreira, Jose; Olhero, Susana
The carbon nanotubes are emerging as innovative tools in nanobiotechnology. However, their toxic effects on the environment and health have become an issue of strong concern. In the present study, we demonstrate biotoxicity test of bone cement based on functionalised carbon nanotube reinforced PMMA/HA for next generation biomedical applications. The biotoxicity of f-MWCNTs was tested in triplicate against Gram-negative bacteria Escherichia coli JM 109. The above observations indicate that f-MWCNTs do not inhibit the growth of E. coli cells when compared to cultures not amended with f-MWCNTs. The phase composition and the surface morphology of the nanocomposite material were studied using X-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), and micro-Raman. Additionally, nano or macro mechanical properties of f-MWCNTs-reinforced nanocomposite were performed by a nanoindentation technique and 3-point bending test, respectively. The test indicates that 0.1% concentration in weight of f-MWCNTs in the PMMA/HA nanocomposite material gives the best mechanical properties.